Porosity and sealing ability of root fillings with gutta-percha and BioRoot RCS or AH Plus sealers. Evaluation by three ex vivo methods - Viapiana, R. [UNESP]; Moinzadeh, A. T.; Camilleri, L.; Wesselink, P. R.; Tanomaru Filho, M. [UNESP]; Camilleri, J. (Wiley-Blackwell, 2015)
To investigate the ability of BioRoot RCS, a tricalcium silicate-based root canal sealer and AH Plus to effectively fill the root canals of contralateral teeth using three evaluation methods, and to investigate also the correlation between the methods. The prepared root canals of ten pairs of contralateral mandibular premolar teeth were filled with gutta-percha and sealer using lateral compaction. The percentage of voids within the root canal was assessed by micro-computed tomography, whilst sealing ability was investigated by fluid transport and leakage of fluorescent microspheres. The interaction of sealer with dentine, and sealer penetration were assessed by confocal microscopy. The void volume, fluid flow, microsphere leakage and sealer interaction with dentine for both materials were compared. Nonparametric (Mann-Whitney) tests were used to compare the % void and fluid transport of the two sealers. Spearman correlation was used to assess the pairwise relationships between the techniques. The level of significance was set to 0.05. BioRoot RCS exhibited significantly more percentage of voids than AH Plus. There was no difference in fluid flow and microsphere penetration. BioRoot RCS exhibited a different pattern of sealer penetration and interaction with the dentine walls compared to AH Plus. For both materials, the pairwise correlations between the three techniques were close to zero, indicating weak relationships. MicroCT analysis revealed a higher void volume for BioRoot RCS. The other techniques did not show a difference between the sealing ability of the sealers. The correlation between the three ex vivo methods of assessment was weak demonstrating their complementarity rather than their concordance.
Keywords: Bioroot rcs; Contralateral teeth; Fluid transport; Leakage studies; Micro-computed tomography; Tricalcium silicate